A model of significant wave height for reliability assessment of a ship - Podgorski, Krzysztof; Rychlik, Igor (Journal of Marine Systems, 2014)
Significant wave heights are modeled by means of a spatial–temporal random Gaussian field. Its dependent structure can be localized by introduction of time and space dependent parameters in the spectrum. The model has the advantage of having a relatively small number of parameters. These parameters have natural physical interpretation and are statistically fitted to represent variability of observed significant wave height records. The fitted spatial–temporal significant wave field allows for prediction of fatigue accumulation in ship details and of extreme responses encountered. The method is exemplified by analyzing a container ship data relevant for North Atlantic trade and the results show a high agreement with actual on-board measurements.